Multiplex real‐time PCR assay for the detection of three invasive leafminer species: Liriomyza huidobrensis, L. sativae and L. trifolii (Diptera: Agromyzidae). Issue 2 (18th August 2016) - Sooda, Anuradha; Gunawardana, Disna; Li, Dongmei; Kumarasinghe, Lalith
Abstract: Rapid and precise identification of immature stages of leafminers of the genus Liriomyza Mik associated with imported fresh produce is essential to ensure appropriate biosecurity decisions at the border, in quarantine and post border. The leafminers Liriomyza huidobrensis, Liriomyza sativae and Liriomyza trifolii are not present in New Zealand and classified as regulated pests when detected at New Zealand's border. To assist rapid species identification of the immature stages of interceptions, a multiplex real‐time TaqMan PCR assay was developed to identify these three species simultaneously in a single test. Species‐specific primers and probes were designed by amplifying the mitochondrial COI gene of each targeting species, respectively. The multiplex real‐time PCR assay demonstrated high specificity for all three target species and the assay detected DNA quantities as low as 0.1 pg for all species. Linear responses and high correlation coefficients between the amount of DNA and C q values for each species were also achieved. Therefore, the assay demonstrated its sensitivity and reliability for the identification of these three invasive Liriomyza species.